A Rare Case of Endometrial Cancer Metastatic to the Sigmoid Colon and Small Bowel - Jeffrey A. Hubers; Anurag Soni (Case Reports in Gastrointestinal Medicine)
Metastatic endometrial cancer to the small bowel or colon has been described but is quite rare. We present a case of metastatic endometrial cancer with synchronous metastases to the colon and jejunum identified three years after surgical treatment of early stage endometrial cancer.